"Can I still get a tattoo?" Patients' experiences across the clinical trajectory for metastatic melanoma: a dynamic narrative model of patient journey - Klay Lamprell; Melvin Chin; Jeffrey Braithwaite (The Beryl Institute, 2019)
Advanced and metastatic cancer has a complex diagnostic and management profile that places a heavy long-term burden on patients and healthcare systems. Little attention has been given to patients' experiences across their entire clinical journey. Using a qualitative, longitudinal methodology over a ten-month period, we examined the symptom-to-outcome trajectories of seven people attending a medical oncology clinic at a large, public tertiary referral center in Sydney, Australia. Rather than care being experienced as a largely linear progression through diagnosis, treatment and onto surveillance in which life may return to 'normal', participants are embedded in a cyclical clinical pathway. Recurrence or metastases are not a matter of 'if' but 'when'. This model of the patient journey points to a need for longitudinal, person-centered services to support the growing population of people with melanoma.